Cardiac resynchronization performed by LBBaP‐CRT in patients with cardiac insufficiency and left bundle branch block. Issue 6 (22nd September 2021) - Zu, Linna; Wang, Zefeng; Hang, Fei; Jiang, Yang; Wang, Xinlu; Cheng, Liting; Zhang, Junmeng; Wu, Yongquan
Abstract: Objective: To evaluate the efficacy and safety of left bundle branch area pacing (LBBaP) in patients with heart failure and left bundle branch block (LBBB), and to compare the clinical effects with traditional cardiac resynchronization therapy (CRT). Methods: Thirty‐two patients with dilated cardiomyopathy complicated by cardiac insufficiency and left bundle branch block were divided into CRT group and LBBaP group. Parameters including pacing threshold, R‐wave amplitude, pacing impedance and operation time, and X‐ray exposure time were recorded. The left ventricular ejection fraction (LVEF), left ventricular end‐diastolic diameter (LVEDD), and left ventricular end‐systolic diameter (LVESD) were examined by echocardiography. The changes of QRS complex before and after operation were compared. Results: Compared with CRT group, the LBBaP group spent less time on total operation time and X‐ray exposure time and had stable electrode parameters including pacing threshold, R‐wave amplitude, and lead impedance after 12‐month follow‐up. In addition, LBBaP can achieve narrow QRS complex (117.15 ± 9.91) ms immediately than that in CRT group (130.32 ± 12.41) ms. The change of QRS between LBBaP is (50.30 ± 23.79) ms and CRT group is (33.15 ± 20.22) ms. After 6 months' follow‐up in LBBaP group, EF was higher than that before operation. Followed up for 12 months after operation, EF and LVEDD in LBBaP group were significantly improved compared with those before operation. Conclusion: Left bundle branch area pacing is a safe and effective resynchronization method for patients with cardiac insufficiency and asynchronization, which can achieve same clinical effects to CRT.